THE USE OF ANTI-INFLAMMATORY EFFECT OF THE SORPTION COMPLEX IN REHABILITATION OF PATIENTS WITH CHRONIC HEART FAILURE AFTER MYOCARDIAL INFARCTION - K. Yu. Nikolaev; A. K. Ovsyannikova; G. I. Lifshits; I. V. Moskalenko (Acta Biomedica Scientifica, 2014)
The aim of the study was to investigate the anti-inflammatory effect of minimum dosages of enterosorbent containing carbon and aluminum oxide on the background of standard treatment for patients with chronic heart failure after myocardial infarction. After two weeks of receiving enterosorbent containing carbon and aluminum oxide in patients with CHF (n = 39) showed a reduction in the level of C-reactive protein, as well as marked improvement in microcirculation, which is a manifestation reduce systemic inflammation characteristic of chronic heart failure.